Comparison of glyphosate formulations with and without sequential herbicides for no-till soybean in narrow rows - Ivany, Jerry (Phytoprotection, 2004)
Effective control of weeds during early stages of soybean (Glycine max) growth is critical to minimize crop yield reduction. Experiments were conducted to compare weed control and crop yield with two glyphosate formulations (trimethylsulfonium and isopropylamine salts) applied in the fall or spring, either alone or in combination with sequential pre-or postememergence herbicides in soybean cv. ‘Maple Glen’ no-till planted in narrow rows into grain stubble. In six experiments where glyphosate was applied (three in the fall and three in the spring), there was no difference in weed control or in soybean yield between the two glyphosate formulations. Crop yield was improved over glyphosate used alone by addition of metribuzin in all fall experiments and in two of three spring experiments and by addition of linuron in two of three experiments in both fall and spring. An herbicide that controlled annual broadleaf weeds was needed after fall-applied glyphosate in all experiments to achieve maximum soybean yield. Addition of an effective sequential herbicide after spring applied glyphosate improved yields but not to the same extent as noted with the fall applied glyphosate. A pre-emergence residual herbicide, such as metribuzin or linuron, that controls a broad spectrum of weeds is recommended after fall or spring applied glyphosate to maximize soybean yield.